2018
DOI: 10.14393/bj-v34n5a2018-39463
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological attributes of yellow oxissol under different monocultures in the savanna region of Piauí state

Abstract: Microbial biomass is an important component in maintaining soil quality and plant productivity.The aim of this paper was to evaluate alterations in microbiological attributes and organic carbon in accordance with seasonal change in different monocultures in the Savanna region of Piauí state. Soil samples were collected in areas of soy, eucalyptus, pasture, and in an area of native savanna, at depths of 0-0.20 m, during the rainy and dry periods. Using these samples microbial biomass carbon (MBC), basal respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This expansion, which transforms natural environments into agricultural systems, impacts soil quality indicators because conventional cultivation system are generally adopted during the agricultural exploration of new areas, with soil tillage by heavy machines and the absence of vegetation cover. Thus, in addition to the low nutritional quality of cultivated species, this cultivation system can negatively alter the soil microbiological attributes (Ferreira, Stone, & Martin-Didonet, 2017;Nunes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This expansion, which transforms natural environments into agricultural systems, impacts soil quality indicators because conventional cultivation system are generally adopted during the agricultural exploration of new areas, with soil tillage by heavy machines and the absence of vegetation cover. Thus, in addition to the low nutritional quality of cultivated species, this cultivation system can negatively alter the soil microbiological attributes (Ferreira, Stone, & Martin-Didonet, 2017;Nunes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that integrated production systems promote increases in the carbon contents of microbial biomass as well as in soil enzymatic activity (Balota et al, 2014;Stieven, Oliveira, Santos, Wruck, & Campos, 2014;Nunes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lower values qMIC in agriculture area compared to the other areas indicate that there are lower proportions of labile organic matter and stable soil organic matter (MGANGA; RAZAVI; KUZYAKOV, 2016). qMIC values below 1.0 indicate a slower process for mineralization of OM in these systems (NUNES et al, 2018). Another interesting factor is that in 10-20 cm layer qMIC was superior in all evaluated areas, which may indicate a better quality of SOM, or even a better efficiency of microorganisms in the use of organic compounds in this depth soil.…”
Section: Resultsmentioning
confidence: 89%
“…Another interesting factor is that in 10-20 cm layer qMIC was superior in all evaluated areas, which may indicate a better quality of SOM, or even a better efficiency of microorganisms in the use of organic compounds in this depth soil. Nunes et al (2018), evaluating microbiological attributes in different monocultures in the Cerrado of Piauí state, found a qMIC that varied from (1.06 to 2.66 %). Data that corroborate with presented in this study.…”
Section: Resultsmentioning
confidence: 99%